Модуляция постсинаптических реакций нейронов соматосенсорной коры кошки, активируемых раздражением ноцицепторов, при стимуляции центрального серого вещества, голубого пятна и черной субстанции - Лабахуа, Т.Ш.; Джанашия, Т.К.; Гедеванишвили, Г.И.; Абзианидзе, Е.В.; Ткемаладзе, Т.Т. (Нейрофизиология, 2009)
Исследовано влияние электрической стимуляции центрального серого вещества (ЦСВ), голубого пятна (ГП) и чёрной субстанции (ЧС) головного мозга кошек на постсинаптические процессы, вызываемые в нейронах соматосенсорной коры, которые активировались ноцицептивными влияниями. Досліджено вплив електричної стимуляції центральної сірої речовини (ЦСР), блакитної плями (БП) та чорної субстанції (ЧС) головного мозку котів на постсинаптичні процеси, викликані в нейронах соматосенсорної кори, котрі активувалися ноцицептивними впливами. In experiments on cats, we studied the effects of electrical stimulation of the cerebral central grey (CG), locus coeruleus (LC), and substantia nigra (SN) on postsynaptic processes evoked by nociceptive volleys in somatosensory cortex neurons. Nineteen cells activated exclusively by stimulation of nociceptors (intense stimulation of the dental pulp) and 26 cells activated by both nociceptive and non-nociceptive (near-threshold) stimulations of the n. infraorbitalis and thalamic nucl. ventroposteromedialis (VPM) were intracellularly recorded (nociceptive and convergent cortical neurons, respectively).